Filosofia política, resistência e identidade no baixo Império Romano : um estudo sobre a reação dos filósofos neoplatônicos ao avanço do cristianismo (361-363) - Pereira, Fernanda Coimbra da Costa (2009)
In 361 A.D., Emperor Julian took on the empire and publicly declared his preference for the pagan system of beliefs, which had been severely losing prestige due to the rise of Christianity and the works of Constantine and Constantius II. Since in the Later Roman Empire, the emperor’s religious choice suggested not only a personal option, but also a political one, Julian’s attempt to reestablish paganism as the religious basis of the empire implied also in rejecting the basilea, the Christian-Hellenistic royalty that had been consolidating. Therefore, Julian needed a new political thought to legitimate his authority before the roman society in association with the precepts of the pagan religion. Thus, he invited the neoplatonic philosophers to live at court and help him in this task since these philosophers had been converted, in a process of identity reformulation, into divine men, spokespeople for paganism. Therefore, in the role of representatives of a religious system that was being distorted so that Christianity could be consolidated as the only one with the means for salvation, they elaborated a series of strategies to oppose this process. Strategies that can be identified in Lives of the Sophists, by Eunapius of Sardis, which portraits the lives of these philosophers converted into theioi andrés. We can then see a representation fight between two religions, pagan and Christian, for the monopoly of the holy ground. In this context of cultural clash, one of the strategies of opposition elaborated by paganism was the development of a political philosophy, which was adopted by Julian right in the beginning of his government. In order to identify this theoretical concept of power, we resort to Letters and to a satire named Misopogon, written by the emperor in the city of Antioquia, while he was preparing for a military expedition against the Persians, in which he died, in 363.